Penerapan Sistem Marketing Digital dan Non-Digital pada Perusahaan PDAM - Derby Khoirulloh Sesandi (Pusat Riset dan Inovasi Nasional, 2023)
Karawang Regional Drinking Water Company is a regional company engaged in the supply of drinking water for the City of Karawang, especially in the Kec. East Teluk Jambe. Unequal distribution constraints and service capacity that still needs to be increased are the reasons for the importance of PDAM Tirta Tarum, Karawang City in implementing the right marketing strategy in order to provide excellent service to customers. The aims of this research are: to identify the marketing strategy that has been implemented by the Regional Drinking Water Company (PDAM) Tirta Tarum, Karawang City, to identify the internal and external environment faced by PDAM Tirta Tarum, Karawang City; formulate the most appropriate marketing strategy for the Regional Drinking Water Company (PDAM) Tirta Tarum, Karawang City based on qualitative methods. The research is limited to the identification and analysis of internal and external strategic factors that influence decision making in the field of marketing at PDAM Tirta Tarum, Karawang City. The results of this research are expanding the distribution network, increasing the intensity of promotions through print media, electronic media and social media, reducing the level of water loss and conducting socialization on saving water and providing a payment system for installation on credit specifically for residents with middle to lower economic class.